Un modello di accrescimento con differenziazione sessuale per l’anguilla europea ( Anguilla anguilla ) - Bevacqua, Danièle; Melià, Paco; Crivelli, Alain Jean; De Leo, Giulio Alessandro; Gatto, Marino (HAL CCSD, 2005)
International audience